2010
DOI: 10.1016/j.neuron.2010.02.014
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Role for the Striatum in the Pathogenesis of the Cognitive Symptoms of Schizophrenia

Abstract: The cognitive symptoms of schizophrenia are largely resistant to current treatment and are thus a life-long burden of the illness. Studies of cognitive symptoms have commonly focused on prefrontal cortex because of its demonstrated importance for executive function and working memory—key components of the deficit. The role of striatal-cortical circuitry and therefore the striatum itself has received much less attention. Here we review longstanding evidence that the striatum and its cortical connections are cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
306
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 425 publications
(322 citation statements)
references
References 112 publications
(136 reference statements)
13
306
0
3
Order By: Relevance
“…We analyzed this cerebral region as some evidence points to the existence of striatal hyperdopaminergic activity secondary to hypofunction of the prefrontal dopamine system [32,33], whereas D 2 R and A 2A R are expressed mainly in medium-sized GABAergic spiny neurons [6]. Interestingly, a recent study showed that, in rodent, ecto-5′-nucleotidase is specifically expressed in this neuronal population, being responsible for most of the extracellular adenosine produced in the striatum [34].…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed this cerebral region as some evidence points to the existence of striatal hyperdopaminergic activity secondary to hypofunction of the prefrontal dopamine system [32,33], whereas D 2 R and A 2A R are expressed mainly in medium-sized GABAergic spiny neurons [6]. Interestingly, a recent study showed that, in rodent, ecto-5′-nucleotidase is specifically expressed in this neuronal population, being responsible for most of the extracellular adenosine produced in the striatum [34].…”
Section: Discussionmentioning
confidence: 99%
“…Schizophrenia is typically characterized by three symptom clusters: positive (eg, hallucinations, delusions, disordered thoughts), negative (eg, flattened affects, social withdrawal), and cognitive (eg, attention and working memory deficits) (Simpson et al, 2010). This disease has traditionally been associated with a deregulated dopaminergic system, mainly because of the fact that for many years typical antipsychotics (ie, strong dopamine (DA)-D 2 receptor antagonists such as haloperidol) have served as the mainstream pharmacotherapy for psychotic patients (Keshavan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Following the demonstration that loss of function of the 5-HT 2B receptor in Htr 2B − / − mice confers a wide spectrum of schizophrenic-like behavioral phenotypes, we show that selected phenotypes are induced by acute pharmacological blockade of 5-HT 2B receptors with RS127445 (selective 5-HT 2B receptor antagonist) and rescued by chronic antipsychotic treatment with the typical antipsychotic drug haloperidol. The dorsal striatum (dSTR) and its connections with the prefrontal cortex (PFC) have been implicated in the pathogenesis of both the positive and the cognitive symptoms of schizophrenia (Howes et al, 2009;Simpson et al, 2010). Indeed, neurochemical alterations in the dopaminergic and glutamatergic corticostriatal circuits underlie a substantial portion of the dysfunction seen in schizophrenic patients (Gordon, 2010;Howes et al, 2009;Keshavan et al, 2008;Simpson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There was a negative correlation between connectivity between the mPFC M a n u s c r i p t 18 and the left iPFC and performance IQ. Prefrontal striatal connectivity has been linked with cognitive functioning in schizophrenia [71,72] as well as in other populations [73][74][75]. The striatum and cortex are anatomically and functionally linked through several cortico-striatal-thalamic-cortical circuits [76] and pathologies of the striatum affect cognition in a similar manner to pathologies of the prefrontal cortex [77].…”
Section: Iq -Neuroimaging Correlationsmentioning
confidence: 99%